Pessoa idosa': um estudo de representações no parque municipal de idosos em Manaus. - Valamatos, Sâmela de Freitas (2024)
This is an interdisciplinary survey, with a qualitative and descriptive approach, produced from the perspective of the human sciences. Its basic theories were Moscovici's theory of Social Representations, Bourdieu's theory of Symbolic Power, Foucault's theory of Disciplinary Power, and Bauman, Laraia and Geertz's theories of culture. The questions posed in this research were based on the legislation in force in our country, which states that anyone aged 60 or over is an 'elderly person'. The following question was therefore formulated: “How does a person feel when they reach the age of 60 and have their life classification immediately and arbitrarily defined as now being an ‘elderly person’?”. The general objective of this research was: “to capture the social representation attributed by people over 60 years of age to the classificatory term ‘elderly person’” and the specific objectives were: “to understand what the term ‘elderly person’ means to the participants in the research”; “to identify whether the term ‘elderly person’ is representative of the participants in the research” and, “to record how the participants in the research feel about the classification and/or possibility of classification ‘elderly person’”. In order to meet these objectives, this research carried out a survey of data from the subjects themselves on the term 'elderly person', interviewing 18 participants in activities at the Parque Municipal do Idoso, located in the city of Manaus, all of whom were aged 60 or over. This research met its specific objectives, finding the following certainties: the term 'elderly person' is a complex web that encompasses an indeterminate number of representations and meanings, presenting points of connections and ruptures, of encounters and mismatches, with participants being inadequately reduced into columns of macro aspects, making it necessary to categorize as many classifications as there are participants in order to understand what is represented by the term in an individual way. 83% of the participants share an 'elderly person'. None of the participants felt violated if they were addressed by the name 'elderly person', some pointed out that what offended them was violent treatment and cited 'old man' as an example. The research tool was an open-ended structured interview, so other data was found, detailed and evident that: being an 'elderly person' represents being at the mercy of a plurality of biological, psychological, social and labor characteristics. Being an 'elderly person' means experiencing various moments in which ageism is practiced by others around them, regardless of their age. To be an 'elderly person' is to be a modern person by a term that represents the security of rights and guarantees and to have them violated in several, if not all, spheres and to be at the mercy of violence, including in these spheres. Finally, one survey also reported that to be an 'elderly person' with the opportunity to attend an elderly living center is to experience care, affection, respect, consideration, esteem and various other good treatments